Forensic anthropological standards for cranial sex estimation in Canada: preliminary results. (29th July 2019) - Noble, Jacqueline; Flavel, Ambika; Aviv, Richard; Franklin, Daniel
ABSTRACT: In forensic investigations of unknown skeletal remains, a biological profile is used to narrow the pool of potential matches in the missing person's database; one of the important components of that profile is the accurate estimation of skeletal sex. The current study involves the morphometric quantification of cranial sexual dimorphism in a Canadian population for the specific purpose of developing predictive models for the estimation of sex. The main aim of this study is, therefore, to quantify the accuracy methods of said existing sex estimation models as applied to a Canadian population and thereafter devise population-specific standards. The current study represents the retrospective analysis of 400 (190 female, 210 male) multiple detector computed tomography (MDCT) scans collected from the Sunnybrook Health Sciences Centre in Toronto, Ontario. Preliminary results indicate that current methods of cranial skeletal sex estimation illicit unacceptable classification accuracy rates when applied to this sample.